Effects of cathodal transcranial direct current stimulation to primary somatosensory cortex on short-latency afferent inhibition. Issue 11 (5th August 2015) - Kojima, Sho; Onishi, Hideaki; Miyaguchi, Shota; Kotan, Shinichi; Sugawara, Kazuhiro; Kirimoto, Hikari; Tamaki, Hiroyuki
Abstract : The aim of this study was to investigate the effects of cathodal transcranial direct current stimulation (tDCS) applied over the primary somatosensory cortex (S1) on short-interval afferent inhibition (SAI). Thirteen healthy individuals participated in this study. Cathodal tDCS was applied for 15 min at 1 mA over the left S1. Motor-evoked potentials (MEPs) were measured from the right first dorsal interosseous muscle in response to transcranial magnetic stimulation (TMS) of the left motor cortex before tDCS (pre), immediately after tDCS (immediately), and 15 min after tDCS (post-15 min). SAI was evaluated by measuring MEPs in response to TMS pulses applied 40 ms after peripheral electrical stimulation of the index finger. For each measurement period (pre, immediately, and post-15 min), MEP amplitude was significantly smaller when TMS followed index finger stimulation (SAI condition) than when TMS was delivered alone (single TMS) ( P <0.01), indicating expression of SAI. The MEP ratio (MEP of SAI/MEP of single TMS) at post-15 min was significantly larger than that of pre ( P <0.05), indicating suppression of SAI. However, no significant difference was observed between pre and immediately, and immediately and post-15 min. These results suggest that cathodal tDCS applied over the S1 causes a decrease in S1 excitability following peripheral electrical stimulation and cathodal tDCS applied over the S1 decreased the inhibitory effects of SAI.